Microdissection and microcloning of the mouse X chromosome. - Fisher, E M (1985)
A wild mouse (CD) karyotype in which all the chromosomes bar the X, 19, and Y, are fused as metacentrics has been used for the microdissection and microcloning of a specific mouse X chromosome region. Dissection of a proximal region of the X chromosome encompassing the genetic loci Hprt to Tfm and including mdx has yielded 650 clones. A number of the recovered clones containing sizable inserts have been confirmed as X chromosome specific. This X chromosome bank of clones provides a start point for the isolation of the mdx locus. It is now clear that microdissection and microcloning can be applied to all mouse chromosomes, including the X chromosome, yielding premapped banks of clones that will greatly aid in the isolation and characterization of important genetic loci.